Evaluation of the economic viability of circular models in agriculture based on neutrosophic cognitive maps - Alvarez-Bernuy, Silvia Marina (2024)
The main purpose of this evaluation is to analyze the economic viability of the implementation of circular models in agriculture in Tarma, Peru. This involves examining the costs and benefits associated with the adoption of circular practices, as well as identifying possible barriers and opportunities for their implementation at the local level. By better understanding the economic landscape, it will be possible to inform decision-making both at the government level and at the level of individual farmers. For the analysis, we have a committee of 30 experts who will evaluate the relationship between variables that positively or negatively affect the implementation of these models in the town. The tool selected for the analysis is Neutrosophic Cognitive Maps, which includes an indeterminacy component within the calculations. This allows greater accuracy in the results since indeterminacy is an inherent part of prediction.